SEC applies whistleblower protections to confidentiality agreements. Issue 3 (7th September 2015) - Adams, Daniel; Chunias, Jennifer; Hale, Robert; Newell, John; Goldberg, William T.
Abstract : Purpose: – The article highlights one of several recent SEC enforcement developments involving whistleblowers. Design/methodology/approach: – The article describes a recent SEC enforcement action based on confidentiality provisions of a company agreement, highlights the provision that the SEC found to be a violation of federal securities laws as amended by the Dodd-Frank Act, and summarizes several other related recent federal regulatory developments. The article suggests actions that companies may wish to take in light of the SEC's enforcement action in this case. Findings: – The SEC's expansive view of the Dodd-Frank Act whistleblower protections may require companies to undertake a broad review of confidentiality provisions in various agreements and policies. Practical implications: – Companies should review all confidentiality provisions in light of the KBR enforcement action to determine which agreements, policies and other documents may require amendment to avoid violating the Dodd-Frank whistleblower protections under the federal securities laws. This potentially includes employment-related agreements, HR materials, various other legal documents, and corporate codes of conduct, among others. Originality/value: – The article presents the reasons and practical suggestions for review of confidentiality provision in company agreements, policies and other documents.